Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/ldr.3778
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the sediment transport capacity from flow condition and particle size in the presence of vegetation cover

Abstract: The sediment transport capacity plays a pivotal role in erosion research, and is usually predicted using hydraulic variables. The transport capacity and hydraulic variables are affected by vegetation cover. Our understanding of the effect of vegetation cover, including the size, density, and arrangement of vegetation stems, on the relationship between the sediment transport capacity and hydraulic variables were rather limited. The objectives of this study were to investigate the effect vegetation stem cover on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…This disturbance results in the loss of a stable surface roughness, leading to the need for a portion of the shear stress to counteract the ensuing instability, as a consequence, the form shear stress acting on the soil may decrease (Ding & Fu, 2022). Additionally, when taking into account the presence of vegetation stem cover, relying solely on the τ value may not accurately predict sediment transport capacity, as emphasized in the study by Mu et al (2020). Similarly, Yang et al (2017) and Shi et al (2019) reported weak linear relationships between the τ value and surface roughness in their experimental investigations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This disturbance results in the loss of a stable surface roughness, leading to the need for a portion of the shear stress to counteract the ensuing instability, as a consequence, the form shear stress acting on the soil may decrease (Ding & Fu, 2022). Additionally, when taking into account the presence of vegetation stem cover, relying solely on the τ value may not accurately predict sediment transport capacity, as emphasized in the study by Mu et al (2020). Similarly, Yang et al (2017) and Shi et al (2019) reported weak linear relationships between the τ value and surface roughness in their experimental investigations.…”
Section: Discussionmentioning
confidence: 99%
“…The hydraulic parameters on a slope are influenced by various complex factors, including vegetation, rainfall characteristics, terrain slope, and soil type (Pan, Ma, & Wainwright, 2016a; Shen et al, 2016). Vegetation plays a pivotal role in attenuating the kinetic energy of raindrops and overland flow on hillslopes and in changing sediment particle transport patterns (Li et al, 2023; Mekonnen et al, 2016; Mu et al, 2020; Wen et al, 2023). Clipping management, as a primary means of regulating vegetation, has significant value in protecting ecology and improving economic benefits (Shahzad et al, 2012; Wang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have studied T c under different experimental conditions, including variations in the vegetation/stem basal cover (Ding et al, 2020; Mu et al, 2019; Snelder & Bryan, 1995), median diameter (Mu et al, 2021), and hydrostatic pressure head (Wang et al, 2020). To further illustrate the influence of these conditions on T c , a new and more accurate equation was established by using these parameters with the traditional hydrodynamic parameters to predict T c .…”
Section: Introductionmentioning
confidence: 99%
“…Many predicted equations have been established for sheet/overland flow (Guy et al, 2009; Li et al, 2011), rill/concentrated flow (Knapen et al, 2009; Tekwa et al, 2016), and interrill flow (Abrahams et al, 2000; Li & Abrahams, 1999; Zhang et al, 2018). Researchers have determined that hydrodynamic variables, including the flow velocity ( V ), shear stress ( τ ), stream power ( w ), unit stream power ( P ), and unit energy ( E ), considerably influence T c (Ali et al, 2012; Ding et al, 2020; Fu et al, 2020; Knapen et al, 2009; Mu et al, 2021; Nord et al, 2009; Shih & Yang, 2009; Wang et al, 2016; Wu et al, 2018). Previous studies have shown that each parameter may be the optimal predictor for estimating T c under different experimental conditions (Ali et al, 2012; Hessel & Jetten, 2007; Knapen et al, 2009; Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation